Continuous dopaminergic stimulation in a patient treated with daytime Levodopa-carbidopa intestinal gel and overnight Rotigotine: a case report. - Imbriani, Paola; Schirinzi, Tommaso; D'Elia, Alessio; Pisani, Antonio (Acta Biomedica Atenei Parmensis, 2017)
Patients with Parkinson’s disease (PD) receiving long-term L-Dopa therapy eventually develop motor complications with unpredictable “on-off” response fluctuations and involuntary movements, leading to progressive disability. Hence, the search for alternative therapeutic choices based on continuous dopaminergic stimulation (CDS) becomes crucial for the treatment of advanced PD. Here, we describe the case of a 70-year-old man with a 9-year history of PD, treated with daytime levodopa-carbidopa intestinal gel (LCIG) and overnight Rotigotine transdermal patch. LCIG monotherapy significantly reduced motor fluctuations and prevented the appearance of unpredictable off periods; concurrently, overnight Rotigotine improved his sleep quality and morning akinesia. Both LCIG and Rotigotine induce CDS, which conceptually mimics physiologic striatal dopamine receptor function. Hence, they both represent a good therapeutic option for the treatment of advanced PD.